Exergy analysis and genetic algorithms for the optimization of flat-plate solar collectors - Kalogirou, Soteris A. (My University, 2012)
This paper employs exergy analysis to derive a general equation for the exergy efficiency of flat plate collectors and thus optimize its design and operation. Exergy analysis of a flat-plate solar collector is a more effective method of finding the optimum relationship between flow rate and the collector area. The fixed parameters in this optimization are the collector inlet temperature, available solar radiation, the collector transmittance-absorptance product and the ambient temperature. The collector heat loss coefficient is estimated according to the collector plate temperature, wind convection loss, number of glass covers, collector inclination, ambient temperature and emittance of collector plate and glass cover. In order to find the optimum value of this multivariable problem genetic algorithms are used which are based on the principles of genetics and survival of the fittest. The optimization parameter is exergy efficiency and the objective is to maximize this parameter. Genetic algorithms proved suitable and very quick in obtaining the required results. These results prove that the exergy efficiency of a flat-plate solar collector is maximized for small distances between the riser tubes and for very small diameter of these tubes. By using a more practical distance of 10 centimetres between the tubes, and excluding this parameter from the optimization procedure, very small differences are observed in maximum exergy efficiency and if the cost of the materials is accounted this is a more cost-effective solution. Other findings are that the exergy efficiency increases considerably at higher solar radiation and that the transmittance absorptance product affects to a great extent the exergy efficiency.
Keywords: Costs; Efficiency; Energy conversion; Exergy; Glass; Optimization; Solar collectors; Solar radiation; Sun; Temperature; Tubes (components); Cost-effective solutions; Exergy Analysis; Flat-plate collector; Flat-plate solar collectors; Optimisations; Optimization parameter; Optimization procedures; Survival-of-the-Fittest; Genetic algorithms